AI-Powered Chatbots of ChatGPT: Exploring the Potentials and Challenges in English Teaching and Learning Process - Tira Nur Fitria (Universitas Sulawesi Barat, 2025)
In the era of rapid digital transformation, innovations such as ChatGPT have significantly influenced various sectors, particularly education. This library-based research examines the potential benefits and challenges of using ChatGPT in the teaching and learning process. The findings indicate that ChatGPT, a natural language–based artificial intelligence developed by OpenAI, can generate human-like responses and function as a virtual assistant by providing feedback, information, and interactive dialogue. Its educational benefits include personalized learning, immediate feedback, interactive communication, support for teaching materials, enhanced learner autonomy, improved language skills, critical thinking development, and increased student motivation and engagement. However, the use of ChatGPT also presents notable challenges, including risks of biased or inaccurate information, ethical concerns, data privacy issues, plagiarism, overreliance on technology, and the potential marginalization of teachers’ roles. To maximize benefits while minimizing risks, educational institutions should integrate ChatGPT as a supportive learning tool rather than a replacement for educators, promote ethical and responsible use, establish clear policies, adapt curricula to digital developments, encourage critical engagement, and continuously monitor technological advancements. Therefore, further empirical research is needed to examine the effective, ethical, and context-sensitive integration of ChatGPT in diverse educational settings.